Pelatihan Pencatatan Laporan Keuangan Sederhana dan Pengenalan Keseimbangan Perekonomian Dua Sektor pada Santri Yayasan RH La Tahzan Cinangka, Depok – Jawa Barat - Purwatiningsih, Purwatiningsih; Sari, Silvia; Septiowati, Rini (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Recording financial reports is an important activity in accountancy. Financial reports are not only needed by companies but also individuals. Santri become part of accounting with carry out monthly money management records. In general, students find it difficult to record financial reports clearly, in detail and systematic. The purpose of service is to train students record simple financial reports in manage money. The service team uses training methods through four stages. Lectures, tutorials, discussions and evaluations. The service was held at the RH La Tahzan Islamic boarding school, Cinangka Village, Sawangan District, Depok City, West Java Province on April 26 2024, which was attended by 25 students. The result of this training is that students take part in training with enthusiastic. Delivery of material is light, according to needs, and easy understood, direct training assistance, discussions exciting, sufficient training duration, and evaluation as a measure of success. Students are helped and Able to record financial reports simply. This is as efforts to manage students' finances and minimize waste.